Improving The Ability to Dig Up Information on Historical Texts In Grade VI Elementary School Students With the Cooperative Integrated Reading Composition (CIRC) Method Assisted by Mind Mapping - Eponiah; Wikanengsih (JLER (Journal of Language Education Research), 2026)
The ability to explore important information in historical narrative text is one of the important abilities that must be possessed by elementary school students in Indonesian language materials. Based on the analysis of pretest results of grade VI students on the ability of students to dig up important information in historical texts at SDN Karawang Wetan III, it was found that students still had difficulty in classifying information using aspects: what, who, when, where, why, and how. This study aims to determine whether there is a significant difference in the skill of digging up information on historical texts between groups of students taught using the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by Mind Mapping and groups of students taught not using the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by Mind Mapping for grade VI students at SDN Karawang Wetan III, East Karawang District, 2022/2023 academic year. This research is a pseudo-experiment. This research design is a non-equivalent post-test only control group design. The population of this study were all grade VI students at SDN Karawang Wetan III, East Karawang District, totaling 106 students. The research sample was class VI B students totaling 35 people as the experimental class and class VI C students 35 people as the control class. The data collection method was carried out by the test method, namely with an objective test instrument (multiple choice). The data obtained were analyzed using descriptive statistical analysis techniques and t-test inferential statistical analysis techniques. The results of the analysis showed that the average score of students' historical text information retrieval skills using the CIRC learning model assisted by mind mapping was 23.47 and students who were taught not using the CIRC learning model assisted by mind mapping was 16.09. Hypothesis testing using t-test shows that t-count > ttabel (t-count = 7.73 > ttabel =1.99714). Based on the results of the study, it can be concluded that there is a significant difference in the skills of digging up historical text information between students who are taught using the learning model (CIRC) assisted by mind mapping and students who are taught not using the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by mind mapping in class VI at SDN Karawang Wetan III for the 2022-2023 academic year.